STUDENTS’ PROGRAMMING SKILLS IN DESIGNING VISUAL BASIC–BASED MATHEMATICS CALCULATION APPLICATIONS - Nashrullah Mailisman; Nailul Authary; Cut Fitriani (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2025)
This study aims to describe students’ programming skills in designing mathematics calculation applications based on Visual Basic as an outcome of the Programming Language course. The research employed a descriptive quantitative approach involving students who had completed the course. Data were collected through a project-based assignment in which students developed mathematics calculation applications and were assessed using a programming skills rubric covering algorithm design, code implementation, user interface design, and application functionality. The research instrument was validated through expert judgment and tested for reliability to ensure measurement consistency. Data were analyzed descriptively to provide a comprehensive overview of students’ programming skills. The results indicate that students were able to integrate programming concepts and mathematical principles into functional applications. Students also demonstrated a good understanding of program logic and the use of Visual Basic syntax, although there remains room for improvement in algorithm efficiency and interface design. Overall, the findings suggest that the Programming Language course contributes positively to students’ ability to develop mathematics calculation applications in accordance with the intended learning objectives.